Systemic spread of measles virus: overcoming the epithelial and endothelial barriers - Ludlow, Martin; Allen, Ingrid; Schneider-Schaulies, Jürgen (Thrombosis and haemostasis, 2009)
As the major entry receptor, signalling lymphocytic activation molecule (SLAM, CD150) essentially determines the tropism of measles virus (MV) for immune cells. This receptor is of considerable importance for the induction of immunomodulation and -suppression, and for the systemic spread of MV to organs including secondary lymphoid tissues, the skin, the respiratory tract, and the brain predominantly via infected cells of the immune system. But how does the virus cross the epithelial barrier during initiation of the infection, the blood organ barriers formed by endothelial cells, and the epithelial barrier from within, when virus will be released from the host? Additional unknown receptor(s) on CD150-negative epithelial and endothelial cells have been postulated. However, it has also been postulated (and demonstrated in macaques) that the initial infection is independent from usage of this receptor, and that the first target cells appear to be CD150-positive cells in the epithelium. For later stages of the infection, for virus release from the host, it is claimed that this unknown receptor on epithelial cells is required for crossing the barrier from within. The endothelial cell barrier must be crossed from the apical (luminal) to the basolateral (abluminal) side to carry the infection to organs and the skin. However, infected leukocytes are impaired in several functions including transmigration through endothelial cells. The infection may spread via cell contact-mediated infection of endothelial cells and basolateral virus release, or via migration of infected leukocytes.